2018
DOI: 10.4184/asj.2018.12.2.202
|View full text |Cite
|
Sign up to set email alerts
|

APSS-ASJ Best Clinical Research Award: Predictability of Curve Progression in Adolescent Idiopathic Scoliosis Using the Distal Radius and Ulna Classification

Abstract: Study DesignProspective study.PurposeTo determine the risk of clinically significant curve progression in adolescent idiopathic scoliosis (AIS) based on the initial Cobb angle and to test the utility of the distal radius and ulna (DRU) classification in predicting these outcomes.Overview of LiteratureDetermining the remaining growth potential in AIS patients is necessary for predicting prognosis and initiating treatment. Limiting the maturity Cobb angle to <40° and <50° reduces the risk of adulthood progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 34 publications
1
19
1
Order By: Relevance
“…With regard to surgical decision-making, brace weaning at stage 7 of sTW3 and R9U7 of DRU shows a high risk of curve progression [18], and a Cobb angle of >40° at stage 7 is associated with a significantly high risk of curve progression to >50° at skeletal maturity or the need for surgical treatment [19]. It is also possible to predict the possible Cobb angle at skeletal maturity using DRU staging and the Cobb angle at the first outpatient clinic visit; thus, both would be useful for surgical decision-making [20].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to surgical decision-making, brace weaning at stage 7 of sTW3 and R9U7 of DRU shows a high risk of curve progression [18], and a Cobb angle of >40° at stage 7 is associated with a significantly high risk of curve progression to >50° at skeletal maturity or the need for surgical treatment [19]. It is also possible to predict the possible Cobb angle at skeletal maturity using DRU staging and the Cobb angle at the first outpatient clinic visit; thus, both would be useful for surgical decision-making [20].…”
Section: Discussionmentioning
confidence: 99%
“…One study which compared laminoplasty versus laminectomy and fusion for patients with multi-level OPLL showed that laminectomy and fusion was superior in maintaining cervical lordosis compared to laminoplasty in patients with OPLL [ 58 ]. There was also no significant difference in pre-operative and post-operative JOA scores of patients in either approach so both methods could achieve similar clinical improvement [ 58 ]. There was no significant difference in the rate of C5 palsy and axial pain with either approach but laminectomy and fusion had more blood loss ( P < 0.03) [ 58 ].…”
Section: Anterior Vs Posterior Approachmentioning
confidence: 99%
“…There was also no significant difference in pre-operative and post-operative JOA scores of patients in either approach so both methods could achieve similar clinical improvement [ 58 ]. There was no significant difference in the rate of C5 palsy and axial pain with either approach but laminectomy and fusion had more blood loss ( P < 0.03) [ 58 ]. Another study showed that laminectomy and fusion was able to significantly reduce the OPLL growth rate compared to laminoplasty [ 46 ].…”
Section: Anterior Vs Posterior Approachmentioning
confidence: 99%
“…1 The main aim of nonoperative treatment is to prevent curve progression and adulthood progression. 2,3 However, the options of nonoperative treatment are highly variable without clear consensus. 4,5 Standardization of care is important to improve overall healthcare efficiency as well as for comparative research.…”
Section: Introductionmentioning
confidence: 99%
“…Journal of Orthopaedic Surgery 28(2) least 14 years for girls and 16 years for boys. Most (49.4%) selected a gradual weaning protocol of brace-wear time reduction over the course of 6 months, while 25.3% switched to nocturnal wear for 3-12 months, and 21.7% selected immediate weaning.…”
mentioning
confidence: 99%